2022
DOI: 10.1039/d2dt02241a
|View full text |Cite
|
Sign up to set email alerts
|

Sterics and metal-ion radius control the self-assembly of [M2L3] helicates

Abstract: The interplay of many factors influences the outcomes of self-assembly reactions. Using an acetylene-appended quaterpyridine ligand we show that both the size of metal ion and the presence of steric...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…45 We attribute the formation of Zn 2 L 3 but not Fe 2 L 3 helicates to a combination of the metal's ionic radius and ligand's steric bulk increasing the energy of the Fe 2 L 3 relative to the Fe 4 L 6 self-assembly, as has been observed in related systems. 46,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 We attribute the formation of Zn 2 L 3 but not Fe 2 L 3 helicates to a combination of the metal's ionic radius and ligand's steric bulk increasing the energy of the Fe 2 L 3 relative to the Fe 4 L 6 self-assembly, as has been observed in related systems. 46,47…”
Section: Resultsmentioning
confidence: 99%
“…45 We attribute the formation of Zn 2 L 3 but not Fe 2 L 3 helicates to a combination of the metal's ionic radius and ligand's steric bulk increasing the energy of the Fe 2 L 3 relative to the Fe 4 L 6 self-assembly, as has been observed in related systems. 46,47 The spin-crossover properties of cages 1-11 were investigated in solution between 248 K and 348 K in CD 3 CN. While the Evans method 48 can determine the magnetic susceptibility from variable-temperature (VT) NMR experiments, preliminary studies with cage 6 showed the NMR signals shifted upon addition of the p-xylene standard, suggesting possible guest binding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the proteins are intrinsically dynamic, metal cations of distinct labile nature can provide a valuable source to investigate dynamic properties of the assembled cages for protein‐mimicking, allowing twisted configurations around metal centers to increase diversity of cage structures [7] with stereochemical merits [7a,8] . The six‐coordinated first‐row transition metals, such as Fe 2+ , Ni 2+ and Zn 2+ , have been widely applied in cage assembly, focusing on the shape and size control of the cage containers; [3l,9] however, their significance in cage dynamics and functions should not be neglected [3k,10] . When it comes to a large cage composed of multiple metal centers, the tiny change on individual metal center may be amplified or synergized, leading to macroscopically visible disparities.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 When metal ions with larger ionic radii were employed, helical assemblies could be exclusively formed with L 1 . 43 In each of these assem-blies, the strong positive stereochemical communication between octahedral metal centres was not disrupted by the steric bulk of the acetylene groups resulting in homochiral assemblies. Here we present chiral derivatives of L 1-2 in which resolved stereogenic centres have been introduced through a copper(I) catalysed 1,3-cycloaddition (L [3][4] ).…”
mentioning
confidence: 99%
“…S8 †), approximately the same size as observed for related helicates. 43 Red crystals, suitable for X-ray structure determination, were grown by methanol diffusion into a solution of the iron(II) complex in acetonitrile. The product crystallised in space group P2 1 and the asymmetric unit contains both S,S,S, S,S,S,ΔΔ-[Fe 2 L 3 3 ] 4+ and S,S,S,S,S,S,ΛΛ-[Fe 2 L 3 3 ] 4+ diastereomers of the complex (Fig.…”
mentioning
confidence: 99%